2014
DOI: 10.1038/nm.3770
|View full text |Cite
|
Sign up to set email alerts
|

The Ashwell-Morell receptor regulates hepatic thrombopoietin production via JAK2-STAT3 signaling

Abstract: The hepatic Ashwell-Morell receptor (AMR) can bind and remove desialylated platelets. We demonstrate that platelets become desialylated as they circulate and age in blood. Binding of desialylated platelets to the AMR induces hepatic thrombopoietin (TPO) gene transcription and translation, thereby regulating platelet production. The highly conserved endocytic AMR signals through Janus kinase 2 (JAK2) and the acute phase response signal transducer and activator of transcription 3 (STAT3) in vivo and in vitro. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
282
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(316 citation statements)
references
References 51 publications
(64 reference statements)
5
282
3
6
Order By: Relevance
“…The production of platelets is highly regulated, because this is important to prevent serious bleeding when platelet counts are low, as well as to prevent vascular occlusion and organ damage when platelet counts are increased. Recently, it was elegantly shown that platelet production can be regulated by binding of desialylated platelets to the hepatic Ashwell-Morell receptor, which induces expression of TPO in the liver via JAK2-STAT3 signaling (133).…”
Section: Infections and Thrombocytopeniamentioning
confidence: 99%
“…The production of platelets is highly regulated, because this is important to prevent serious bleeding when platelet counts are low, as well as to prevent vascular occlusion and organ damage when platelet counts are increased. Recently, it was elegantly shown that platelet production can be regulated by binding of desialylated platelets to the hepatic Ashwell-Morell receptor, which induces expression of TPO in the liver via JAK2-STAT3 signaling (133).…”
Section: Infections and Thrombocytopeniamentioning
confidence: 99%
“…Platelets desialylate as they circulate, thereby becoming the primary ligand for the AMR, 10 and this interaction regulates hepatocyte thrombopoietin production. 11 Desialylation also occurs when platelets are activated by several physiological stimuli, and AMR clearance may be relevant in attenuating the coagulopathy of sepsis. [12][13][14] Our results support the indications of international ITP guidelines, 15 which suggest that both PSSs and glycoprotein-specific antibody testing are not mandatory in ITP workup or management.…”
mentioning
confidence: 99%
“…Compared with platelet transfusion, the degree of the improvement in the liver function was small, although adverse events did not occur. A recent report stated that the aging of platelets controls the production of TPO (Grozovsky et al 2015); thus, the aging and activation of platelets are involved in liver regeneration. During this clinical trial, no cancerous lesions were observed, which may ensure the safety of EP concerning cancer in patients with hepatitis and LC.…”
Section: Discussionmentioning
confidence: 99%